Grain size effect on softening behaviour of Al-Mg alloy due to paint bake heat treatment - Nadarajah, Hemalatha (2007)
Aluminium- Magnesium (Al-Mg) alloys have very good formability properties and have been used extensively for interior structural components of automotive Body in White (BIW). The alloys in an annealed temper achieve their strength through work hardening mechanism during press forming process. The strengthening mechanism is due to Mg atoms in solid solution exerting dislocation drag during low temperature plastic straining. However at elevated temperatures, high diffusivity of Mg atoms allows easy dislocations rearrangements which lead to reduction of mechanical strength. This phenomenon is called softening. Furthermore, accumulation of stored energy in the dislocations substructures due plastic straining during press forming process also serves as a large driving force for thermal recovery. These two factors contribute Al-Mg alloy sheet to be susceptible to softening during paint bake cycle. Al-Mg sheets for automotive Body in White (BIW) applications are normally supplied in an annealed condition known as "-0-" temper. The microstructure of an annealed sheet is characterized by equiaxed recrystallized grains. Average size of grains depends on actual rolling schedule and heat treatment stages on those particular sheets. This project investigates the effect of varying grain size on softening characteristics of pre-strained sheets after paint bake cycle. This is done by annealing Al-Mg H32 sheets in different temperatures to obtain different grain size. Smaller grain size would have more softening than larger grain size.